PENGARUH PROFITABILITAS, AKTIVITAS PERUSAHAAN, LIKUIDITAS, SOLVABILITAS, DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN - Ahfas, Mahfuz (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to examine the effect of profitability, company activity, liquidity, solvency, and financial distress on going concern audit opinion in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research method used is quantitative with logistic regression analysis, as the dependent variable is dichotomous (going concern vs. non-going concern). Secondary data was obtained from audited annual financial statements. The results show that profitability and liquidity have a significant negative effect on going concern audit opinion, while solvency and financial distress have a significant positive effect. Company activity does not have a significant effect. These findings imply that auditors consider specific financial indicators as signals of a client's going concern risk